A Discourse-Pragmatic Study of Lecturer and Student Conversations in English Literature Course - Ahmad Ridwan; Shafruddin Tajuddin; Eva Leiliyanti (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aimed to explain and describe (1) the speech acts used in the conversation between lecturers and students in English Literature Course; and (2) the intentions behind the conversation between lecturers and students in English Literature Course. This study used a qualitative research method. Data collection was analyzed using listening and note-taking techniques. The analysis technique was implemented using the flowing technique. The results of this study can be concluded as follows: (1) lecturers and students used locutionary, illocutionary, and perlocutionary speech acts in learning; (2) the purposes contained behind the lecturers' and students' utterances, among others: to instruct, motivate, clarify, reinforce, entertain, and conclude. Thus, the conversations between lecturers and students used direct and indirect speech acts in English Literature Course.